Peptide-rich extracts from leaves of newbouldia laevis (P. Beauv.) seem. ex. bureau (bignoniaceae) with antimicrobial and brine shrimp lethality activities (2024)
Global concerns over antibiotic-resistant microbial pathogens have spurred a quest for innovative, stable, and target-specific molecules like bioactive peptides. This study evaluates the antimicrobial properties and toxicity of peptide-enriched extracts from Newbouldia laevis leaves. Aqueous extraction, thin layer chromatography (TLC), and Phenomenex's Stratum Giant Tube C18-E were used to obtain partly purified fraction (PPF) and crude peptide extracts (CPE). Antimicrobial inhibitory capacity was determined using p-INT dye, with gentamicin and fluconazole as standards. Cytotoxicity was assessed with Artemia salina nauplii. Microsoft Excel and GraphPad Prism 5 was used in analysing the data. Peptides were detected in CPE and PPF via TLC and modified G-250. PPF demonstrated more efficacy (IC50: 5.89μg/mL to 33.94μg/mL) against bacteria and fungi, with low toxicity (LC50: 5964.87μg/mL for PPF and 1094.20μg/mL for CPE) in the Brine shrimp lethality assay. The study presents the discovery of bioactive peptides from the leaves of Newbouldia laevis. Consequently, bioactive peptides extracted from this plant hold potential as foundational compounds for the development of novel broad-spectrum antibiotics aimed at combating microbial infections.